ARTIFAK SAKRAL DALAM BUDAYA IBAN DI SARAWAK = SACRED ARTIFACTS IN IBAN CULTURE IN SARAWAK - Gregory, Kiyai @ Keai; Noria, Tugang (Penerbit Universiti Sains Malaysia, 2023)
This article focuses on social hierarchy and ethnographic observation research based on cultural artifacts that are considered to have sacred value in Iban culture in Sarawak. Sacred artifacts are cultural objects that are believed to have spiritual values and mystical powers that are capable of protecting and bringing harmony to their owners if executed according to customs and rituals. This belief is driven by the ancestral religion of Pengarap Lama and the habitat that has been home to the Iban community since time immemorial. In proving the critical findings, qualitative-based research methods have been implemented based on in-depth observations, interviews, and documentation. The research findings found that sacred artifacts are still important in the culture of the Iban community even though they have embraced new religions such as Islam and Christianity. Therefore, in preserving the significant value of sacred artifacts in Iban culture, this article is an effort to archive the culture of the various races community in Sarawak, especially the Iban community.